Knowledge, attitude and practice in relation to effects of probiotics in food among Medical Faculty students in a Malaysian Public University - Azman, Hazirah (2016)
Probiotic food products have been introduced in Malaysia since 1990’s and have been claimed as a beneficial food to human health and human intestines. The objective of this study was to determine the significant difference in level of knowledge, attitude and practice on effects of probiotics in food among Faculty of Medicine and Health Sciences UPM students. There were 222 respondents involved in this study which mainly from undergraduate and postgraduate students in medical and health sciences programmes. Self-administered questionnaires were given to the respondents and it contained Section A: Socio-demographics, Section B: Knowledge on probiotics, Section C: Attitudes on probiotics and Section D: Practices on probiotic consumption. The results indicated that majority of the respondents had poor knowledge (50.5%), negative attitude (56.8%) and poor practice (70.3%) towards probiotics and probiotic food products. The chi-square results showed that there was significant difference in knowledge with practice (X2= 4.59, p= 0.03) and attitude with practice (X2= 6.28, p= 0.01). However, there was no significant difference in knowledge with attitude (X2= 0.18, p= 0.67). As a conclusion, majority of the respondents had poor knowledge, negative attitude and poor practice. It is recommended that the respondents should be exposed to health talk on probiotics or a probiotic training program conducted by the probiotic food manufacturers in enhancing their knowledge about probiotics.